The puzzle of domination in society : seeking solutions in the African context - Madonko, Thokozile (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2006)
The presence of human destitution, impoverishment and degradation in the midst of plenty has puzzled social thinkers for millennia. One of the oldest and grandest of theories: the theory of ideology attempts to provide an answer to the puzzle of domination in society. Michael Rosen, in his book On Voluntary Servitude (1996), argues that the solution provided by the theory of ideology is problematic. Furthermore, on the basis of his critique, Rosen argues that we should abandon the theory of ideology and consider alternatives to it. Even though many contemporary academics have turned away from the theory of ideology, because they view it as an imprisoning meta-theory, this study explores the possibility of there being a meta-theory that could help us to make sense of the world. Through an examination of Rosen's critique this thesis shows that Rosen is too quick in his dismissal of the theory of ideology because he fails to consider that a revised functionalist theory of ideology can be expanded to account for the mechanism(s) that ensure that, over time, the society in question acquires ideological consciousness to further its welfare. This thesis shows that Rosen is correct in his criticism of the theory of ideology's explanation of domination because the content, history and social effects of ideological consciousness cannot be fully explained in terms of their role in promoting or stabilising relations of domination. In light of Rosen's criticism the thesis shows that if one provides both an explanation of the psychological motivations of individuals and of the nature of the oppressive society in which they find themselves then what I call an integrated theory of ideology can be developed. In order to illustrate the importance of an integrated theory of ideology the study moves away from high-level theoretical abstraction to concrete social analyses, focusing on the work of Frantz Fanon and Steve Biko and their explanations of domination. The reason this study focuses on their work is because in their role as social scientists, Fanon and Biko provided a powerful critique of colonial, post-colonial and neo-colonial society. It will be argued that Fanon and Biko were able to provide a lasting critique of colonial reality because they offered their critique within the framework of such an integrated theory. Consequently, this study argues that, as Fanon and Biko's work illustrate, an integrated theory of ideology qua critical theory ought not to be abandoned because it is crucial for understanding and resisting forms of oppression that exist in the world today.
Keywords: Rosen, Michael. On voluntary servitude; Fanon, Frantz, 1925-1961; Fanon, Frantz, 1925-1961 -- Political and social views; Biko, Steve, 1946-1977; Ideology; Black people -- Race identity; Ideology -- Psychological aspects; Ideology -- Sociological aspects; Power (Social sciences); Consciousness; Racism